2020
DOI: 10.1163/15685381-bja10024
|View full text |Cite
|
Sign up to set email alerts
|

Sources of intraspecific morphological variation in Vipera seoanei: allometry, sex, and colour phenotype

Abstract: Snakes frequently exhibit ontogenetic and sexual variation in head dimensions, as well as the occurrence of distinct colour morphotypes which might be fitness-related. In this study, we used linear biometry and geometric morphometrics to investigate intraspecific morphological variation related to allometry and sexual dimorphism in Vipera seoanei, a species that exhibits five colour morphotypes, potentially subjected to distinct ecological pressures. We measured body size (SVL), tail length and head dimensions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…4 ). Assuming that sexual maturation occurs at 325 mm of SVL (Lucchini et al 2020 ; Espasandín et al 2022 ), we indicate that helminths were mostly found in adults of V . seoanei .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…4 ). Assuming that sexual maturation occurs at 325 mm of SVL (Lucchini et al 2020 ; Espasandín et al 2022 ), we indicate that helminths were mostly found in adults of V . seoanei .…”
Section: Discussionmentioning
confidence: 53%
“…seoanei (Espasandín et al 2022 ) and frequently relate to the ecology of the Iberian viper species (e.g. Martínez-Freiría et al 2008 , 2015 ; Lucchini et al 2020 ; Chamorro et al 2021 ). Further information on how they were obtained can be found in Espasandín et al ( 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In reptiles, body length correlates to age due to an undetermined growth throughout their life (Candan 2021). Indeed, assuming 325 mm as SVL at sexual maturation (Lucchini et al 2020;Espasandín et al 2022) we indicate that helminths were mostly found in adults of V. seoanei. This agrees with results from other reptile species in which body length also has a signi cant effect on the occurrence of parasites.…”
Section: Biological and Eco-geographic Factors Related To Helminth Oc...mentioning
confidence: 79%
“…However, nuclear markers are needed to address reproductive isolation and the extent of gene flow among divergent lineages, aiding in clarifying their taxonomic status [ 15 ]. Vipera seoanei , on the other hand, exhibits a shallow genetic structure and low genetic diversity at the mtDNA level [ 16 ], that contrasts with its high morphological and colouration polymorphism [ 17 , 18 ]. The use of microsatellite loci has the potential to provide a detailed perspective on the genetic diversity and structure of populations and the factors contributing to their phenotypic variation.…”
Section: Introductionmentioning
confidence: 99%